Pharmacists' perceptions on real-time prescription monitoring (RTPM) systems – a cross-sectional survey - Ziyue Zhang; Lin Guo; Ran Si; Leanne Chalmers; Patricia Filippin; Jane Carpenter; Petra Czarniak (Exploratory Research in Clinical and Social Pharmacy, 2022)
Background: Real-time prescription monitoring (RTPM) systems are an effective tool to help health practitioners monitor opioid use and reduce opioid-related harm but little has been reported about the support required by pharmacists to engage with them effectively in practice. Objective: To evaluate the current understanding and perceptions of Western Australian pharmacists regarding RTPM systems and opioid-related harm, and investigate their self-reported training and support requirements prior to RTPM system implementation. Methods: This cross-sectional, prospective study involved an online Qualtrics survey distributed to Western Australian community or hospital pharmacists involved in dispensing and patient-centred roles via local professional pharmacy newsletters and social media. Data collection included demographic information, responses to authentic case scenarios and Likert-scale questions regarding perceptions and training requirements of a RTPM system, pain management and opioid-related harm. Descriptive analysis was utilised. Result: Sixty-two pharmacists responded to the questionnaire. Most (58/61; 95.1%) had a positive attitude towards RTPM systems, but only 33/61 (54.1%) reported being prepared for its implementation. Perceived barriers to successful implementation included lack of remuneration (46/60; 76.6%), conflict with prescribers (40/60; 66.7%), increased workload (37/60; 61.7%), staff safety concerns (34/60; 56.7%) and lack of knowledge regarding RTPM systems (32/60; 53.3%). Even though most participants were satisfied with training previously received, over 90% reported requiring further training and education, especially regarding RTPM systems (51/57; 96.2%) and opioid-related harm (56/57; 98.2%). Conclusion: Among a small sample of participants, there was a strong positivity regarding the value of RTPM systems and a high degree of receptiveness to further training in preparation for RTPM implementation.